Preparation and characteristics of gelatin sponges crosslinked by microbial transglutaminase - Haiyan Long; Kunlong Ma; Zhenghua Xiao; Xiaomei Ren; Gang Yang (PeerJ, 2017)
Microbial transglutaminase (mTG) was used as a crosslinking agent in the preparation of gelatin sponges. The physical properties of the materials were evaluated by measuring their material porosity, water absorption, and elastic modulus. The stability of the sponges were assessed via hydrolysis and enzymolysis. To study the material degradation in vivo, subcutaneous implantations of sponges were performed on rats for 1–3 months, and the implanted sponges were analyzed. To evaluate the cell compatibility of the mTG crosslinked gelatin sponges (mTG sponges), adipose-derived stromal stem cells were cultured and inoculated into the scaffold. Cell proliferation and viability were measured using alamarBlue assay and LIVE/DEAD fluorescence staining, respectively. Cell adhesion on the sponges was observed by scanning electron microscopy (SEM). Results show that mTG sponges have uniform pore size, high porosity and water absorption, and good mechanical properties. In subcutaneous implantation, the material was partially degraded in the first month and completely absorbed in the third month. Cell experiments showed evident cell proliferation and high viability. Results also showed that the cells grew vigorously and adhered tightly to the sponge. In conclusion, mTG sponge has good biocompatibility and can be used in tissue engineering and regenerative medicine.